Skimmed, Lactose-Free Milk Ingestion Postexercise: Rehydration Effectiveness and Gastrointestinal Disturbances Versus Water and a Sports Drink in Physically Active People - Aragón Vargas, Luis Fernando (2024)
This is the complete dataset used for the publication Skimmed, Lactose-Free Milk Ingestion Postexercise: Rehydration Effectiveness and Gastrointestinal Disturbances Versus Water and a Sports Drink in Physically Active People. The header for each variable (column) includes a comment explaining it. For complete methods, please see the complete manuscript in the International Journal of Sport Nutrition and Exercise Metabolism, https://doi.org/10.1123/ijsnem.2023-0253